More information, better diet?―regression-discontinuity evidence from hypertension diagnoses in China - Qihui Chen; Juerong Huang; Yue Hu; Jiale Bao (Humanities & Social Sciences Communications)
Abstract Hypertension is diagnosed when one’s systolic blood pressure (SBP) reading exceeds 140 mmHg or his/her diastolic blood pressure (DBP) reading exceeds 90 mmHg. Exploiting these diagnostic rules, this paper identifies the causal impact of hypertension diagnoses on one’s diet structure by performing a two-dimensional regression discontinuity analysis. Our analysis of a longitudinal dataset on 9355 Chinese adults from a large-scale household survey revealed mixed effects of first-ever hypertension diagnoses based on SBP readings and little impact of DBP-based diagnoses. SBP-based diagnoses help reduce individuals’ (already overconsumed) fat and livestock product intake about 3 years later. However, SBP-based diagnoses also undermine individuals’ dietary diversity and diet balance by reducing their consumption of foods that should be increased for hypertensive individuals (e.g., fruits). These previously overlooked undesirable effects suggest that even though disease diagnoses can provide patients with accurate and professional health information, patients may misunderstand and misinterpret the information provided, thus leading to unhealthy dietary responses.